La sinologie : la langue chinoise créée par les sinologues ? - Clément Fabre (Revue d’Histoire des Sciences Humaines)
What place was assigned to the Chinese in the study of their own language, in 19th-century French sinology? To judge by Chinese Studies in Paris, which was fraught with rival conceptions of sinology, each of which appealed to a different definition of the Chinese language, no clearcut answer is possible. Although there was no wholesale rejection of the competence of the Chinese, there was no unanimous recognition of their value either. Instead, several antagonistic constructions of the Chinese language envisaged several different roles for the Chinese, depending on the situations and strategies involved. Whereas the “book-bound” sinologists described an ancient Chinese tongue which was no longer understood in China itself, and which remained accessible only in Paris, the “field” sinologists, ever keen to undermine their colleagues' prestige, affirmed that Chinese was a language unchanged since the dawn of time, and that the Chinese were authorities in it. The non-specialist Press, for its part, had difficulty grasping the idea that anyone could claim greater expertise in the Chinese language than a Chinese person.